2022
DOI: 10.3390/life12111904
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Presentation and Prognosis of Takayasu Arteritis with or without Stroke or Transient Ischemic Attack—A Retrospective Cohort Study

Abstract: Takayasu arteritis (TAK) could cause a stroke or transient ischemic attack (TIA) in young individuals due to inflammatory vascular occlusion or intracerebral hemorrhage. We compared the clinical presentation, angiographic features, longitudinal patterns of disease activity, medical treatments, and survival in 34 TAK patients with stroke/TIA and 157 without stroke/TIA from a single-center retrospective cohort. TAK patients with stroke/TIA were older (p = 0.044) with a greater proportion of males (p = 0.022), mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Such patients are diagnosed incidentally on examination with findings of an absent pulse, asymmetrical blood pressure on the limbs, and vascular bruit. Inadequate collateral leads to signs of claudication, whereas abrupt vascular occlusion leads to ischemic complications and end organ damage like stroke and myocardial infarction without any preceding constitutional symptoms 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such patients are diagnosed incidentally on examination with findings of an absent pulse, asymmetrical blood pressure on the limbs, and vascular bruit. Inadequate collateral leads to signs of claudication, whereas abrupt vascular occlusion leads to ischemic complications and end organ damage like stroke and myocardial infarction without any preceding constitutional symptoms 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Embolus can be of cardiac origin or from distant thrombosed arteries like the carotid. Takayasu arteritis can present with hypertensive emergencies leading to hemorrhagic stroke as well, and stroke as an initial presentation of Takayasu arteritis is common in older patients 5 . Our patient presented with signs and symptoms of an acute MCA stroke, making it an unusual case.…”
Section: Discussionmentioning
confidence: 99%
“…In the aforementioned study, the main causes of death included mesenteric ischemia (25%) and aortic aneurysm rupture (25%) [ 96 ]. Interestingly, Misra et al reported a similar risk of mortality in TAK patients with and without stroke/TIA (HR; 1.38, 95% CI 0.19–10.20) after adjustment for gender, age of disease onset, delay to diagnosis, baseline disease activity, and number of conventional or biologic/targeted synthetic immunosuppressants used [ 97 ]. Thus, stroke and TIA do not appear to adversely affect survival in TAK patients [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…For reasons not yet clear, vascular inflammation in TAK heals with a greater degree of fibrosis (resulting in arterial stenosis) than in the counterpart large vessel vasculitis (LVV) of giant cell arteritis (GCA), where arterial dilatation occurs more often ( 4 6 ). Stenosis in TAK can result in critical downstream ischemia ( 7 ) leading to myocardial infarction or ischemic stroke ( 7 ) which can occur even during inactive disease ( 8 ).…”
Section: Introductionmentioning
confidence: 99%